Early intervention of anterior crossbite and unfavorable tongue posture with a prefabricated myofunctional appliance: A case report - Putri Ganesha Asturini; Nieka Adhara Wahono (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Anterior crossbite in the primary dentition may be an early indicator of a developing Class III malocclusion. Clinical findings, hereditary factors, and environmental influences, such as breathing problems and tongue posture, should be considered for early intervention. Purpose: This case report describes the early diagnosis and intervention of anterior crossbite and unfavorable tongue posture as potential risk factors contributing to a Class III growth pattern. Case: An 8-year-old girl with a history of preterm birth and a familial history of Class III malocclusion presented with the chief complaint: lower teeth in front of upper teeth. Clinical findings included anterior crossbite in the primary canines, mild lower incisor crowding, and mesiocclusion in both second primary molars. The cephalogram revealed bimaxillary retrusion (SNA = 79°, SNB = 74°), a skeletal Class I (ANB = 4°, Wits = –2 mm), and a forward tongue posture. Case Management: An ENT specialist diagnosed the patient with allergic rhinitis, without any airway obstruction. A prefabricated myofunctional appliance was prescribed to guide the eruption of permanent teeth into their ideal positions, eliminate maxillary growth restriction, and retrain tongue posture. The anterior crossbite of the primary teeth and the crowding were corrected within 9 months. Use of the appliance is ongoing until all permanent incisors have fully erupted and ideal occlusion is achieved. Conclusion: Myofunctional therapy during early mixed dentition may serve as a beneficial interceptive treatment to retrain orofacial muscles and guide the eruption of permanent teeth into an ideal occlusion.